2014
DOI: 10.1186/1471-2377-14-69
|View full text |Cite
|
Sign up to set email alerts
|

Self-Management education for adults with poorly controlled epILEpsy (SMILE (UK)): a randomised controlled trial protocol

Abstract: BackgroundTeaching people with epilepsy to identify and manage seizure triggers, implement strategies to remember to take antiepileptic drugs, implement precautions to minimize risks during seizures, tell others what to do during a seizure and learn what to do during recovery may lead to better self-management. No teaching programme exists for adults with epilepsy in the United Kingdom although a number of surveys have shown patients want more information.Methods/DesignThis is a multicentre, pragmatic, paralle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 33 publications
1
37
0
1
Order By: Relevance
“…Exclusion criteria were having non-epileptic seizures only, having seizures related to an acute illness or substance overuse, having a serious psychiatric condition or terminal illness, and participating in other epilepsy-related studies [12]. …”
Section: Methodsmentioning
confidence: 99%
“…Exclusion criteria were having non-epileptic seizures only, having seizures related to an acute illness or substance overuse, having a serious psychiatric condition or terminal illness, and participating in other epilepsy-related studies [12]. …”
Section: Methodsmentioning
confidence: 99%
“…The trial was conducted and reported in accordance with the Consolidated Standards of Reporting Trials (CONSORT) guidelines. A detailed description of the trial design, interventions, and outcome measures can be found in the published trial protocol . Here we provide a brief overview.…”
Section: Methodsmentioning
confidence: 99%
“…Randomization was provided by an online system managed by the King's Clinical Trials Unit, maintaining full allocation concealment . Randomization occurred in blocks of 2 (1:1 intervention: control) and was stratified by treatment center.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations